Screening of lactic acid bacteria with immune modulating property, and the production of lactic acid bacteria mediated fermented soymilk - Sasithorn Sirilun (2018)
© 2017 Bhagavathi Sundaram Sivamaruthi, et al. Background: Lactic acid bacteria (LAB) are reported to have immune activating property. The genetically modified LAB strains producing interleukin (IL) -10 were under consideration for the treatment of inflammatory bowel diseases (IBD). Soybean is rich in necessary nutrients, and the fermented soybean products are known for its health benefits. Aims and Objectives: The current study was aimed to screen LAB with the immune activating property, and production and evaluation of LAB mediated fermented soymilk product. Materials and Methods: Screening of LAB from the fermented foods collected in Chiang Mai. To select a potent LAB strain, the LAB isolates were scrutinized for acid tolerant, bile tolerant, growth rate, antimicrobial ability, adhesion property, and induction of IL-10 production. The physical properties of fermented soymilk (FSM) were evaluated, and in vitro activation of IL-10 by FSM was assessed using Caco-2 cell line. Results: About 742 LAB strains were isolated from 335 fermented food samples. Based on the tested properties, LAB33 was selected as a potent LAB strain, and used for the fermentation of soymilk for 30 days. The LAB33 FSM was superior in quality regarding probiotic nature and microbiological safety. Conclusion: The results of the study suggested that LAB33 is the potent probiotic strain for the production of soymilk-based fermented functional food supplements for the betterment of IBD patients. Further, strain identification is required to register the strain in a public repository, and sustainable utilization for the benefit of mankind.